Foreignization in News Translation: Metaphors in Russian Translation on the News Translation Website InoSMI - Van Poucke, Piet; Belikova, Alexandra (Meta, 2016)
Journalistic texts, as a rule, contain a considerable number of metaphorically used expressions. This paper investigates the handling of metaphors in Russian translations of journalistic texts in order to reveal the different translation strategies used by the translators. The research is conducted in three consecutive steps. First, we identify all metaphors in a twofold corpus of 60 original Dutch, English and Finnish newspaper articles on the one hand, and their corresponding 60 translations into Russian on the other. Secondly, we compare the use of metaphors in the translations with their source texts in order to establish the translation strategies and to determine to which extent the metaphorical expressions in the target texts display a higher degree of foreignness than those used in the source texts. Finally, we analyze the cases of foreignization in the target texts in order to find an explanation for the use of this translation strategy. The investigation shows how foreignization is adopted by the translators in a certain number of specific contexts, making the Western discourse on Russian subjects more visible to the reader, especially in these cases where the source text contains metaphors that suggest a critical interpretation of the Russian state, society or the leaders of the country.